2010
DOI: 10.1111/j.1460-9568.2010.07080.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of decision‐making in a gambling task in older adults with transcranial direct current stimulation

Abstract: Cognitive performance usually declines in older adults as a result of neurodegenerative processes. One of the cognitive domains usually affected is decision-making. Based on our recent findings suggesting that non-invasive brain stimulation can improve decision-making in young participants, we studied whether bifrontal transcranial direct current stimulation (tDCS) applied over the right and left prefrontal cortex of older adult subjects can change balance of risky and safe responses as it can in younger indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 25 publications
5
87
1
Order By: Relevance
“…In a related task, however, only anodal right/cathodal left stimulation improved performance [53] , which is compatible with a risk-avoiding impact of right prefrontal activity. In older participants however, the same electrode arrangement results in more risky behavior, which is possibly caused by age-dependent differences in prefrontal information-processing [54] .…”
Section: Decision-makingmentioning
confidence: 96%
“…In a related task, however, only anodal right/cathodal left stimulation improved performance [53] , which is compatible with a risk-avoiding impact of right prefrontal activity. In older participants however, the same electrode arrangement results in more risky behavior, which is possibly caused by age-dependent differences in prefrontal information-processing [54] .…”
Section: Decision-makingmentioning
confidence: 96%
“…Insert Figure 1 about here Moreover, one comparison study (Boggio et al, 2010) was considered an outlier because the effect value of -1.50 was greater than two standard deviations beyond the standardized mean effect value (red circle). Thus, we removed the outlier study and conducted a subsequent meta-analysis.…”
Section: Overall Tdcs Effects: Standardized Mean Differencesmentioning
confidence: 99%
“…The 25 qualified studies were submitted to our meta-analysis. One author (NK) independently coded the 25 studies and extracted data (Berryhill and Jones, 2012;Boggio et al, 2010;Fertonani et al, 2014;Floel et al, 2012;Goodwill et al, 2015;Goodwill et al, 2013;Hardwick and Celnik, 2014;Harty et al, 2014;Heise et al, 2014;Hoff et al, 2015;Holland et al, 2011;Hummel et al, 2010;Jones et al, 2015;Lindenberg et al, 2013;Manenti et al, 2013;Meinzer et al, 2013;Meinzer et al, 2014;Panouilleres et al, 2015;11 Parikh and Cole, 2014;Park et al, 2014;Ross et al, 2011;Sandrini et al, 2014;Seo et al, 2011;Zhou et al, 2015;Zimerman et al, 2013). Two authors (JS & JC) confirmed data extractions, and all authors were involved in interpreting the meta-analytic results.…”
Section: Study Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…For younger healthy subjects performing risk-taking tasks relevant to gambling, right anodal/left cathodal stimulation over the DLPFC caused the safe prospect to be chosen more frequently, compared to left anodal/right cathodal and sham stimulation [18]. In contrast, for older subjects (age: 50-85 years), left anodal/right cathodal stimulation caused high-risk prospects more often picked compared to sham or right anodal/left cathodal stimulation groups [5]. Cheng and Lee [12] studied risk-taking behavior using tDCS in young healthy subjects.…”
Section: Tdcsmentioning
confidence: 88%